Improvement Physics 1 of Chemistry Learning Outcomes Through Project-Based Learning Models (PjBL) Using Quizizz Online Learning Media - Leony S. L. Purba; Meida E. Marpaung; Nelius Harefa; Anugrah Purba (Jurnal Akademika Kimia, 2021)
Improving cognitive abilities, namely learning outcomes is one of the objectives of learning. Learning outcomes can be improved through the use of creative, innovative learning models in accordance with the current curriculum, the 2013 revised curriculum. This study aims to determine whether there is an increase in Physics Chemistry Learning Outcomes 1 through the Project-based Learning (PjBL) Learning Model using Quizizz online learning media. Based on the results of the normality and homogeneity test, the data is normally distributed with the value of the normality test result of 0.638 (sig 0.05) and homogeneous with the homogeneity test result value of 0.144 (sig 0.05). The results of statistical analysis of research data using the paired t-test hypothesis test results obtained tcount = 17,685 (sig 0.00) and ttable = 0.684 (sig 0.05), it is concluded that there is an increase in learning outcomes in Physics Chemistry 1 through the Project-based Learning (PjBL) learning model using Quizizz online learning media because tcount˃ ttable. A further test is the gain test, to determine the level of improvement in learning outcomes. The results of the analysis using the gain test, the gain value of 42.51%, with the medium category.